KaiXinSan-JiaWei ameliorates cognitive dysfunction in APP/PS1 mice by intervening in gut microbiota and its metabolites - Mana, Lulu; Chen, Fang; Yuan, Xiaoxia (Frontiers in Pharmacology, 2025)
BackgroundAlzheimer’s disease (AD) is a degenerative disease of the central nervous system characterized by progressive cognitive impairment and memory loss. Chinese medicine’s therapeutic effect on AD has become a promising treatment option in recent years, and the Chinese herbal compound Kai Xin San-Jia Wei (KXSJW) is one of its representatives. This study employed a comprehensive approach, including 16S rRNA and Gaschromatography-mass spectrometry (GC-MS) analysis, to investigate the therapeutic efficacy and intrinsic mechanism of KXSJW on AD.Methods50 3-month-old APPswe/PS1dE9 transgenic mice were randomly divided into 5 groups (n = 10): model group (M), donepezil group (Don), KXSJW-low dose group (KJW-L), KXSJW- medium dose group (KJW-M), KXSJW-high dose group (KJW-H), Ten 3-month-old C57BL/6 J wild-type mice were randomly selected as the control group (C). The control and model groups were administered saline by gavage, the donepezil group was administered donepezil (0.92 mg/kg/d), and the KXSJW-low/medium/high dose group was administered KXSJW extract (0.9/1.8/3.6 mL/kg/d); each group was treated once daily for 2 months. The study employed the Morris Water Maze (MWM) to evaluate learning and cognitive abilities. Pathological changes in colon tissue were assessed through hematoxylin and eosin (HE) staining. Analysis of gut microbiota was conducted using 16S rRNA sequencing, and gut microbial metabolite (short chain fatty acids, SCFAs) content was detected using GC-MS. Colonic tissue barrier integrity was examined through immunohistochemistry and western blot, while β-amyloid deposition in brain tissue was assessed. ELISA was used to measure serum intestinal peptide hormones (Glucagon, GHRP-Ghrelin).ResultsKXSJW enhanced learning ability and memory, reduced amyloid deposition in the brain tissue of AD model mice. KXSJW was able to restore the balance of intestinal flora and regulate the concentration of intestinal flora metabolites, especially represented by Firmicutes and its major metabolite butyric acid. Meanwhile, KXSJW restored the intestinal barrier function and improved the release level of intestinal peptide hormones (Glucagon, GHRP-Ghrelin) in AD model mice. This indicates that KXSJW can improve the intestinal internal environment of AD model mice.ConclusionKXSJW may improve the homeostasis of the gut environment in AD, with a focus on the regulation of gut microorganisms and their metabolites, and subsequently improve cognitive impairment in AD. Traditional Chinese Medicine (TCM) has the potential to intervene in AD through multilevel interaction with the brain-gut-axis.